Relationship of Physical Activity and Blood Pressure: Data Analysis of the Integrated Non-Communicable Diseases Development Post (Posbindu PTM) Jenggawah Public Health Center in Jember Regency at 2020 - Maulana, Muhammad Alfin; Susanto, Tantut; Rasni, Hanny; Ma’fuah, Sofiatul; Kurdi, Fahruddin (Journal of Rural Community Nursing Practice, 2023)
Physical activity is one of the factors that can affect the incidence of hypertension. Individuals who lack physical activity will be at risk for hypertension. Therefore, this study aimed to identify the relationship between physical activity and blood pressure participants in non-communicable diseases of integrated development post (Posbindu PTM) Jenggawah Public Health Center, Jember. The retrospective case-control study design was used to analyze secondary data of Posbindu PTM registered from September to November 2020 among 126 participants. Characteristics of participants (age, gender, education, marital and occupational status), physical activity, and blood pressure were measured based on the health chart (KMS) of Posbindu PTM. Among 126 participants in Posbindu PTM identified 58% of having adequate activity and 60% of normal blood pressure. Meanwhile, there was a relationship between physical activity and the blood pressure of Posbindu PTM (χ2=5.795; p-value=0.016). Furthermore, Posbindu PTM participants who had enough physical activity were 0.4 times maintaining the blood pressure (OR: 0.411; 95% CI = 0.198-0.853). Physical activity is correlated with blood pressure among participants in Posbindu PTM. Therefore, the adequacy of physical activity should be improved to maintain blood pressure and prevent the risk of hypertension.